DESIGN OF A HOTSPOT NETWORK WITH A PREPAID SYSTEM USING MIKROTIK AT REDZ GAMING INTERNET CAFE - Meiditra, Irzon; Fauziah; Mutia, Cut; Yuda, Fitra (Journal of Data Analytics, Information, and Computer Science, 2025)
This paper discusses the design of hotspot networks with prepaid systems and to optimize the use of hotspot networks in Warnet Redz Gaming.Manajemen is done by limiting and dividing the network equally according to the price of the voucher purchased. With this paper can help the internet café in optimizing the use of its network. One method that can be used as described is the Queue Tree method. The Queue Tree method functions is to implement more complex functions within the bandwidth limit of the proxy where the use of packet mark has a better function. It is used to limit only one direction of connection either download or upload. Keyword : Bandwidth, Queue Tree, Mikrotik, Mark Packet, Download, Upload